Student Spatial Structure in Realistic Mathematics Education (RME) Approach: Struktur Spasial Siswa Dalam Pendekatan Realistic Mathematics Education (RME) - Quroidah, Anita; Amir, Mohammad Faizal (Universitas Muhammadiyah Sidoarjo, 2021)
Area measurement is the number of measurement units used to cover an area, many students experience low understanding of the concept of measuring the area of ​​an area. Many previous studies have shown that most students find it difficult to measure area. Therefore, the application of the Realistic Mathematics Education (RME) approach can help students to increase knowledge and develop competencies about broad measurement. The measurement of area is not far from the spatial structure, that in order to overcome the weaknesses in understanding the concept of area measurement and encourage a better understanding of area, it must be based on the development of competence in the spatial structure of students through achievement at each level. This study uses a literature study approach. The subject is elementary school students. The data obtained by researchers is from various literatures that have been reviewed and analyzed by researchers. The results of this study are that students can reach every level of the student's spatial structure with the RME approach. And there are differences from students at each level to solve a problem related to the spatial structure of students.